Hybrid green nonaqueous media: tetraethylene glycol modifies the properties of a (choline chloride + urea) deep eutectic solvent. Issue 36 (22nd March 2016) - Kadyan, Anu; Behera, Kamalakanta; Pandey, Siddharth
Abstract : In mixture of a deep eutectic solvent Reline with tetraethylene glycol, inter-species interactions are stronger than the intra-species interactions. Abstract : Deep eutectic solvents (DESs) have emerged as easy-to-prepare inexpensive environmentally benign media with the potential for applications in various areas of chemistry. A judiciously selected cosolvent can modify the properties of a DES in a favorable manner. Tetraethylene glycol (TEG)-modified DES composed of choline chloride and urea in a 1 : 2 molar ratio, named Reline, is investigated over the complete composition regime within 298–358 K for its properties. The empirical solvent polarity parameter, E NT, obtained using the solvatochromic absorbance probe response of a betaine dye, along with Kamlet–Taft parameters, dipolarity/polarizability (π*), H-bond donating acidity ( α ), and H-bond accepting basicity ( β ) suggest the presence of interactions, mainly H-bonded, between TEG and the components of Reline. The H-bond accepting basicity ( β ) of TEG-modified Reline is found to be unusually high. Responses from dipolarity as well as intramolecular charge-transfer fluorescence probes further support these outcomes, suggesting that a small amount of TEG can effectively alter the properties of Reline. Negative molar excess volumes and positive excess logarithmic viscosities estimated from density and dynamic viscosity measurements, respectively, at all compositions and temperatures for (Reline + TEG) mixtures indicate the presence of stronger inter-species H-bonding interactions between Reline–TEG as compared to the intra-species H-bonding interactions between Reline–Reline and between TEG–TEG. FTIR absorbance and Raman spectral measurements indicate unusually high H-bond accepting basicity ( β ) of the (Reline + TEG) mixture to be due to the decreased involvement of urea functionalities in H-bonding with choline chloride, with possible increase in H-bonding between the adequate functionalities of TEG with those of choline chloride.